Espodossolos of Brazil: A review of structure and composition of classes - Andressa Rosas de Menezes; Ademir Fontana; Lúcia Helena Cunha dos Anjos (Revista Brasileira de Ciência do Solo)
ABSTRACT Soil taxonomic systems seek to express pedogenic processes in their classes by choosing attributes or differential characteristics to identify classes at different categorical or hierarchical levels. Due to the advancement of knowledge, classification systems are periodically revised and/or expanded, and this may happen based on the evaluation of the database of these attributes or characteristics for a given class. In this context, the analysis of a broad set of Espodossolos (the equivalent of Spodosols or Podzols) from different pedoenvironments in Brazil is considered relevant to support the improvement of the categorization of this order in the Brazilian Soil Classification System – SiBCS. This study aimed to classify the profiles in the database and, based on their distribution, propose the restructuring of the Espodossolos classes up to the fourth categorical level in the SiBCS. Data from profiles with spodic horizons and the Espodossolos available in the literature, including surveys since 1960, were compiled in an electronic spreadsheet, displaying the morphological, physical, and chemical attributes. In the current edition of SiBCS, there are limitations in clearly separating the Espodossolos at the order and suborder levels due to the definitions adopted for the diagnostic attributes and the control section of the spodic B horizon. From the data base of compiled profiles, at the great group level, the soils are mostly identified in the Órticos class, in the subgroup as espessarênicos, arênicos and típicos, with few profiles or absence of profiles in the êutricos, êutricos arênicos and carbonáticos classes. Based on this assessment, it is proposed, for the order level, the reduction of the control section of the spodic B horizon to start within 2.00 m of depth; for the suborder, a criterion based on the organic carbon contents separating two classes: Humilúvicos and Háplicos. In the great group, based on the criterion of starting depth of spodic B horizon: Hiperespessos, Espessos and Órticos; and in the subgroup to adopt the classes of tiônicos, organossólicos, húmicos, saprolíticos, dúricos, fragipânicos, abrúpticos, hidromórficos, espessarênicos and típicos.